Augumenting the anticancer properties of l-phenylalanine functionalized nanoscopic porous amino acid mimics (Nano-pPAAMs) - Tan, Shao Jie (Nanyang Technological University, 2023)
Therapeutic efficiencies of novel cancer treatment modalities such as photodynamic therapy (PDT) and chemodynamic therapy (CDT) are largely diminished in clinical situations due to the disease’s constantly evolving nature and harsh conditions of the tumour microenvironment (TME); such as insufficiently low intertumoural pH (pH: < 5) and hydrogen peroxide (H2O2) levels. The development of reactive oxygen species (ROS) generating nanomedicine relieves the aforementioned pain points by elevating intertumoural H2O2 levels, typically either via external stimulation (e.g., infrared radiation or ultrasound) or from the innate TME. Their ability to elevate intertumoural H2O2 levels allows them to function as either a standalone anticancer nanomedicine or an adjuvant for follow-up PDT/CDT treatments. L-phenylalanine functionalized nanoscopic porous amino acid mimics (Nano-pPAAMs) stands out amongst the emerging plethora of ROS-generating nanomaterials for their cancer selectivity and intrinsic ability to generate ROS without external stimulation. However, significant high dosages of Nano-pPAAM are required to effectively eradicate the tumour in both in vitro and in vivo studies.